Clinical Outcomes in Patients With Nonobstructive, Labile, and Obstructive Hypertrophic Cardiomyopathy. Issue 5 (25th February 2018) - Lu, Dai‐Yin; Pozios, Iraklis; Haileselassie, Bereketeab; Ventoulis, Ioannis; Liu, Hongyun; Sorensen, Lars L.; Canepa, Marco; Phillip, Susan; Abraham, M. Roselle; Abraham, Theodore P.
Abstract : Background: Hypertrophic cardiomyopathy (HCM) is a common inherited cardiac disease characterized by varying degrees of left ventricular outflow tract obstruction. In a large cohort, we compare the outcomes among 3 different hemodynamic groups. Methods and Results: We prospectively enrolled patients fulfilling standard diagnostic criteria for HCM from January 2005 to June 2015. Detailed phenotypic characterization, including peak left ventricular outflow tract pressure gradients at rest and after provocation, was measured by echocardiography. The primary outcome was a composite cardiovascular end point, which included new‐onset atrial fibrillation, new sustained ventricular tachycardia/ventricular fibrillation, new or worsening heart failure, and death. The mean follow‐up was 3.4±2.8 years. Among the 705 patients with HCM (mean age, 52±15 years; 62% men), 230 with obstructive HCM were older and had a higher body mass index and New York Heart Association class. The 214 patients with nonobstructive HCM were more likely to have a history of sustained ventricular tachycardia/ventricular fibrillation and implantable cardioverter defibrillator implantation. During follow‐up, 121 patients experienced a composite cardiovascular end point. Atrial fibrillation occurred most frequently in the obstructive group. Patients with nonobstructive HCM had more frequent sustained ventricular tachycardia/ventricular fibrillation events. In multivariate analysis, obstructive (hazard ratio, 2.80; 95% confidence interval, 1.64–4.80) and nonobstructive (hazard ratio, 1.94; 95% confidence interval, 1.09–3.45) HCM were associated with more adverse events compared with labile HCM. Conclusions: Nonobstructive HCM carries notable morbidity, including a higher arrhythmic risk than the other HCM groups. Patients with labile HCM have a relatively benign clinical course. Our data suggest detailed sudden cardiac death risk stratification in nonobstructive HCM and monitoring with less aggressive management in labile HCM.